ANALISA KINERJA KEUANGAN PERUSAHAAN BIDANG OTOMOTIF YANG TERDAFTAR DI BEI ( PT. Astra Internasional Tbk) - Pangestu, Fattah Jati; Watini, Katarina (Jurnal Aktual Akuntansi Keuangan Bisnis Terapan (AKUNBISNIS), 2023)
Financial performance is one of important aspect to determine company health. This research is to determine how good is financial performance of PT. Astra International Tbk one of the giant in automotive industry. Financial performance is measured by quantity method by profitability, liquidity and solvability ratio from 2017 to 2022. Result of this research is showed that financial performance of PT Astra International Tbk is on good condition. Based on profitability, liquidity and solvability ratio for 5 years PT. Astra International Tbk need to improve to increasing their sale, but afterall PT. Astra International Tbk had a good job.